KARAKTERISASI PROTEASE DARI ISOLAT BAKTERI ASAL TUMBUHAN RAWA DARI INDRALAYA - Ace Baehaki; Rinto . (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
Proteases constitute one of the most important groups of industrial enzymes, therefore screening of these proteases from bacteria is important. The aim of this study was to characterize proteases from plant swamp bacteria. The result of  proteolytic assays revealed three isolates possesed proteolytic index >1.00 (T1P4, H1P4 and K1P4). The optimum fermentation time of each isolate was 48 hours. The optimum pH of proteases from T1P4, H1P4 and K1P4 was 8.0; 7.5; and 8.0,  respectively. The optimum temperature of T1P4, H1P4 and K1P4 protease was 50 °C; 40 °C;  and 50 °C, respectively. Metal ions (Fe, K, Mn, and Zn) inhibited T1P4 protease except Fe2+ (5 mM), H1P4 protease except  Zn2+ (5 mM),  K1P4 protease except Fe (1 and 5 mM). Effect of inhibtor specific (EDTA) shown EDTA inhibit all  proteases. Study on the effect of metals ion and spesific inhibitors indicated that all protease were  metaloprotease. The moleculer weights of T1P4, H1P4 and K1P4 proteases were determinited by using SDS-PAGE and zymography technique were 151; 138; and 127 kD, respectively.Key words:  bacteria, characterization, protease, swamp